Analisis Penugasan Agen Terhadap Lokasi Nasabah Menggunakan Metode Sperichal Law of Cosines: Analisis Penugasan Agen Terhadap Lokasi Nasabah Menggunakan Metode Sperichal Law of Cosines - Meli, Amelia Safitri (Jurnal INSYPRO (Information System and Processing), 2025)
Abstract - This study aims to determine the most ideal agent location to serve customers in an area using the Spherical Law of Cosines method. In the analysis of agent assignment, determining the distance between the agent and the customer can be calculated precisely using the Spherical Law of Cosines method, thus facilitating more efficient agent assignments and reducing access constraints for customers. It is important to determine an accurate and fast method for calculating the distance between agents and customers. Accuracy results containing reference distance, average distance, and accuracy in percent. The reference shows the kilometer distance ranging from 1 km to 10 km. Average shows the average distance calculated using the Spherical Law of Cosines method, the average distance remains constant at 0.634952 km for all distances. Keywords : Agent assignment analysis, Sperichal Law of Cosines, Costumers